Aneurysmal bone cyst of the cervical spine : case report - Bagić, Irina (Array, 2020)
Aneurysmal bone cyst (ABC) is a non-neoplastic locally destructive primary bone lesion mostly occurring within the first two decades of life with female predominance. Cervical spine ABCs are a very rare clinical entity with particularly demanding surgical resection limited by the involvement of nearby neurovascular structures and a risk for cervical spine instability. We present a case of a 17-year-old patient with a symptomatic ABC of the cervical spine who underwent surgical removal of the osseous lesion with good postoperative outcome. There are different therapeutic strategies for ABC management, but complete surgical removal of the cyst remains one of the most important predictors of favorable outcome, although it can be often limited, especially in the cervical region. Previously described lesions have a very high recurrence rate and therefore different additional methods, such as radiotherapy, embolization and sclerosation have been used in addition to surgical resection. Further studies are necessary for development of evidence-based treatment regimens for cervical spine ABCs in pediatric population.